IoT-Generated Big Data and Security Issues - R.P. Waghamare,; Dr. Bhavana Narain,; Dr. B.T. Jadhav, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Nowadays BD (Big Data) and IoT (Internet of Things) are popular and mostly used terms. The Internet of Things is generating an enormous amount of data. No conventional tool that refers to a massive set of data, such as BD, is available. Speed, Variety and volume are important features of BD, and due to this big data. In this paper, we explore Big data in IoT-driven technologies and the issue of the seven V’s in Big Data. With the rapid growth of IoT, a number of devices are connected. This paper also discusses several cloud-based IoT platforms such as Amazon Web Services and Google Cloud Internet of Things. We studied the importance of Big Data imagining, gives insights on various visualization tools and methods. Lastly, this paper also deals with various significant challenges of Big Data in IoT, security issues and future research directions.
Keywords: IoT; Big Data; Security Issues